2022
DOI: 10.1109/tmtt.2021.3136296
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry of Microelectrodes Array Chips for Electrophysiological Studies Under Simultaneous Radio Frequency Exposures

Abstract: Studying the response of neuronal networks to radiofrequency signals requires the use of a specific device capable of accessing and simultaneously recording neuronal activity during electromagnetic fields (EMF) exposure. In this study, a Microelectrode Array (MEA) that records the spontaneous activity of neurons is coupled to an open transverse electromagnetic (TEM) cell which propagates EMF. We characterize this system both numerically and experimentally at 1.8 GHz. Two MEA versions were compared, for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 36 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…Indeed a recent re-evaluation of the dosimetry (Nefzi et al, 2022) indicated estimated SAR values per Watt of incident power of 5.5 ± 2.3 W/kg and 40.3 ± 5.3 W/kg respectively for the present and former MEA version (El Khoueiry et al, 2018 andMoretti et al, 2013). This reevaluation was made possible thanks to the continuous progress in experimental and numerical dosimetry and better assessment of influencing environmental factors (Nefzi et al, 2022). The SAR level of 28.6 W/kg is however higher than local basic safety restriction fixed at 2.0 W/kg (ICNIRP, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed a recent re-evaluation of the dosimetry (Nefzi et al, 2022) indicated estimated SAR values per Watt of incident power of 5.5 ± 2.3 W/kg and 40.3 ± 5.3 W/kg respectively for the present and former MEA version (El Khoueiry et al, 2018 andMoretti et al, 2013). This reevaluation was made possible thanks to the continuous progress in experimental and numerical dosimetry and better assessment of influencing environmental factors (Nefzi et al, 2022). The SAR level of 28.6 W/kg is however higher than local basic safety restriction fixed at 2.0 W/kg (ICNIRP, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This new design shared the main characteristic of these MEAs namely the amplifier contact pads placed underneath the printed circuit board but presented as main evolutions a reduced chip aperture to the limits of the recording zone and several ground planes in the multi-layered PCB. These evolutions allowed this device to be steadier in terms of Specific Absoption Rate (SAR) and temperature stability during EMF exposure (see Nefzi et al, 2022, for numerical and experimental dosimetry of the device). In this modified MEA, SAR values normalized per 1 Watt of incident power was estimated at 5.5 ± 2.3 W/kg.…”
Section: New Mea Design and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…To enable simultaneous recording and exposure to RF fields, MEAs were maintained “sandwiched” between the TEM bottom plate and the preamplifier (MEA1060-Inv, Multi-Channel Systems, MCS, Reutlingen, Germany), as described in previous publications (El Khoueiry et al, 2018; Merla et al, 2011; Moretti et al, 2013; Nefzi et al, 2022). Once installed on the MEA amplifier, a perfusion holder (MEA-MEM-PL5, ALA Scientific Instruments Inc. USA) was inserted into the MEA chamber.…”
Section: Methodsmentioning
confidence: 99%